Ocena funkcjonalna zawodników uprawiających futbol amerykański z wykorzystaniem testu Functional Movement Screen = Functional evaluation of competitors practicing American football with using Functional Movement Screen test - Kochański, Bartosz; Falkowska, Ewelina; Kałużna, Anna; Kałużny, Krystian; Wołowiec, Łukasz; Hagner-Derengowska, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Kochański Bartosz, Falkowska Ewelina, Kałużna Anna, Kałużny Krystian, Wołowiec Łukasz, Hagner-Derengowska Magdalena, Zukow Walery. Ocena funkcjonalna zawodników uprawiających futbol amerykański z wykorzystaniem testu Functional Movement Screen = Functional evaluation of competitors practicing American football with using Functional Movement Screen test. Journal of Education, Health and Sport. 2015;5(10):170-179. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32588 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A170-179 https://pbn.nauka.gov.pl/works/661276 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Ocena funkcjonalna zawodników uprawiających futbol amerykański z wykorzystaniem testu Functional Movement Screen Functional evaluation of competitors practicing American football with using Functional Movement Screen test Bartosz Kochański1, Ewelina Falkowska2, Anna Kałużna1, Krystian Kałużny1, Łukasz Wołowiec3, Magdalena Hagner-Derengowska2,4, Walery Zukow5 1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Bydgoska Szkoła Wyższa 3II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4Katedra Neuropsychologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 5Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp. Functional Movement Screen (FMS) jest narzędziem służącym do kompleksowej oceny funkcjonalnej. FMS pozwala na ocenę ryzyka wystąpienia kontuzji, ocenę jakości wykonywanych wzorców ruchowych oraz określenie występowania ograniczeń i asymetrii w obrębie narządu ruchu. Cel pracy. Celem pracy jest ocena funkcjonalna zawodników futbolu amerykańskiego z wykorzystaniem testu Functional Movement Screen (FMS) oraz określenie korelacji pomiędzy wynikiem testu FMS, a przebytymi urazami i kontuzjami u zawodników futbolu amerykańskiego. Materiał i metody. Badania przeprowadzono na grupie 30 profesjonalnych zawodników futbolu amerykańskiego reprezentujących klub „KS Bydgoszcz Archers”. Ocenę funkcjonalną wykonano z wykorzystaniem testu Functional Movement Screen. Badania zostały przeprowadzone w trakcie trwania sezonu z wykorzystaniem urządzenia oraz protokołu do testu FMS. Wyniki. Średni wynik w teście FMS uzyskany przez osoby uprawiające futbol amerykański wynosi 14,5/21 punktów. Średnia ocen z większości prób oscyluje koło 2 punktów, co oznacza, że wzorce ruchowe wykonywane są z kompensacją. U zawodników futbolu amerykańskiego zaobserwowano istotną statystycznie korelację pomiędzy przebytymi urazami i kontuzjami, a wynikami osiąganymi w próbie 2, 4 i 6 w teście FMS. Wnioski. 1. U zawodników futbolu amerykańskiego obserwuje się nieprawidłowości we wzorcach mobilności, stabilności oraz koordynacji nerwowo-mięśniowej w teście FMS. 2. Ryzyko wystąpienia kontuzji i urazów u zawodników futbolu amerykańskiego według testu FMS jest relatywnie duże. 3. Wynik testu FMS koreluje z przebytymi urazami i kontuzjami u zawodników futbolu amerykańskiego. Abstract Introduction. Functional Movement Screen (FMS) is a tool for comprehensive functional assessment. FMS allows the assessment of risk of injury, assessment of quality of movement patterns and to determine the occurrence of restrictions and asymmetries within the musculoskeletal system. Aim of the study. The aim of the study is functional evaluation of American football players using Functional Movement Screen (FMS) and to determine the correlation between FMS test result and a history trauma and injuries in American football players. Materials and methods. The study was conducted on a group of 30 professional American football players representing the "KS Bydgoszcz Archers". Functional evaluation was performed by using the Functional Movement Screen. The study was carried out during the season. The study used the device and protocol of FMS test. Results. The average score in the FMS test earned by people practicing American football is 14.5/21 points. The average of the majority of the tests oscillates around two points, which means that the movement patterns are made of compensation. In American football players we observed a statistically significant correlation between a history trauma and injuries, and the results achieved in test 2, 4 and 6 in the FMS test. Conclusions. 1. In American football players observed irregularities in patterns of mobility, stability and neuromuscular coordination in the FMS test. 2. The risk of injury and injury in American football players is relatively high according to the FMS test. 3. FMS test result correlates with a history of trauma and injuries in American football players. Słowa kluczowe: ocena funkcjonalna, FMS, Functional Movement Screen, futbol amerykański. Keywords: functional evaluation, FMS, Functional Movement Screen, American football.